Holocaust odysseys : the Jews of Saint-Martin-Vésubie and their flight through France and Italy - Zuccotti, Susan, 1940- (Yale University Press, 2007)
This book describes the ever-escalating dangers to which Jewish refugees and recent immigrants were subjected in France and Italy as the Holocaust marched forward. Susan Zuccotti uncovers a gruelling yet complex history of suffering and resilience through historical documents and personal testimonies from members of nine central and eastern European Jewish families, displaced to France in the opening years of the Second World War. The chronicle of their lives reveals clearly that these Jewish families experienced persecution of far greater intensity than citizen Jews or longtime resident immigrants. The odyssey of the nine families took them from hostile Vichy France to the Alpine village of Saint-Martin-Vesubie and on to Italy, where German soldiers rather than hoped-for Allied troops awaited. Those who crossed over to Italy were either deported to Auschwitz or forced to scatter in desperate flight. Zuccotti brings to light the agonies of the refugees' unstable lives, the evolution of French policies toward Jews, the reasons behind the flight from the relative idyll of Saint-Martin-Vesubie, and the choices that confronted those who arrived in Italy. Powerful archival evidence frames this history, while firsthand reports underscore the human cost of the nightmarish years of persecution.